Spontaneous retroperitoneal hemorrhage in Menkes disease: A rare case report. Issue 6 (February 2018) - Peng, Chia-Huei; Hsu, Chyong-Hsin; Wang, Nien-Lu; Lee, Hung-Chang; Lin, Shuan-Pei; Chan, Wai-Tao; Yeung, Chun-Yan; Jiang, Chuen-Bin
Abstract: Rationale: Menkes disease (MD), also known as Menkes kinky hair disease, is a fatal neurodegenerative disease caused by a defect in copper metabolism. The symptoms involve multiple organ systems, such as the brain, lung, gastrointestinal tract, urinary tract, connective tissue, and skin. There is currently no cure for this disease entity, and patients with the classic form of MD usually die from complications between 6 months and 3 years of age. Intracranial hemorrhage secondary to tortuous intracranial arteries is a well-known complication of MD, but spontaneous retroperitoneal hemorrhage, to the best of our knowledge, has never been reported in a patient with MD. Herein, we describe the first case of retroperitoneal hematoma as a complication of MD in a 4-year-old boy. Patient concerns: A 4-year-old Taiwanese male patient with MD was referred to the hospital and presented with a palpable epigastric mass. Diagnoses: On the basis of the findings of ultrasonography and enhanced computed tomography, the diagnosis was retroperitoneal hematoma. Interventions: Interventions included laparotomy with evacuation of the hematoma, manual compression, and suture of the bleeding vessels. Outcomes: There were no postoperative complications. Lessons: This case emphasizes that bleeding in patients with MD is possible at any site in the body owing to the unstable structure of the connective tissues. Timely diagnosis with proper imaging studies can lead to prompt and appropriate management and save patients from this life-threatening condition.